Optimization of Calophyllum oil extraction and its application for biogasoline - Kartika, I. A.; Sumbogo, S. D.; Fataya, I.; Trisunaryanti, W.; Hartati, Hartati; Sailah, I. (IOP Conference Series: Earth and Environmental Science, 2022)
The utilization of a binary solvent, i.e. n-hexane-methanol mixture, for Calophyllum oil extraction and resin separation in a direct stage was optimized in this research. Optimum oil yield and separated resin percentage were determined using response surface method with optimizing of extraction time, temperature and stirring speed. Biogasoline production was conducted using thermal cracking at 475-575 ºC of oil obtained from optimum extraction condition. The oil yield was optimized using second order polynomial model. Extraction time affected oil yield more significantly than temperature and stirring speed. Oil yield improved when extraction time, temperature and stirring speed augmented, and the optimum oil yield (59%) was predicted to be reached at 5.3 h, 49 ºC and 385 rpm. Besides, the separated resin percentage was predicted to be constant (20%) with increasing extraction time, temperature and stirring speed so there was no optimum separated resin percentage. The oil obtained from optimum extraction condition showed good quality at 0.91 g/cm3 of density, 45.13 mPa.s of viscosity, 26.4 mg KOH/g of acid value, trace water and sediment content, and zero ash content. The thermal cracking of oil produced 5-79 wt.% liquid product (biogasoline). Biogasoline yield improved as temperature increased from 475 to 575 ºC, and so the highest biogasoline yield (79 wt.%) was obtained at 575 ºC. The GC-MS analysis result of liquid product showed that the biogasoline was composed of C5-C12 fraction (32.2 wt.%), C16-C19 fraction (36.8 wt.%), and nonhydrocarbon fraction (9.4 wt.%).